#TITLE_ALTERNATIVE# - CHANDRA HERMANTO TAMPUBOLON (NIM 13205207); Pembimbing: Dr.Ir. Pekik Argo Dahono, RIO
An analysis and minimization method of output current harmonics in three-level inverter is proposed. The method is based on the Fourier principle applied for inverter output waveforms. The principle is especially useful for threelevel inverter which its modulation is more complicated than two-level inverter modulation. The mean square values of line-to-line output current harmonics in three-level inverter as a function of modulation index are derived. Then, a signal that has to be injected to sinusoidal reference to minimize the output current output is calculated. Minimization method shows that the optimum injections signal is 25% of the third harmonics. Simulation results are included to verify the proposed method.